Late intra-patient tacrolimus trough level variability as a major problem in kidney transplantation: a collaborative transplant study report - Süsal, Caner; Döhler, Bernd (American journal of transplantation, 2019)
Intra-patient variability (IPV) of tacrolimus trough level has been associated with poor outcome after kidney transplantation. These findings were derived from single-center analyses and restricted mainly to measurements early after transplantation. We analyzed in a multicenter effort whether high IPV of tacrolimus levels at posttransplant years 1, 2, and 3 was associated with impaired clinical outcome. More than 6600 patients who received a deceased donor kidney transplant during 2000-2014 and had a functioning graft for >3 years were studied. Graft survival was significantly impaired with increasing IPV (P < 0.001). As compared to patients with a low IPV of <30%, the risk of graft loss during years 4-6 increased 32% in patients with an IPV of 30% to 44% and 66% in patients with an IPV of ≥45% (P = 0.002 and P < 0.001). About one-third of patients showed an IPV of ≥30% with substantially impaired outcome. Even in patients with good outcome during the first 3 posttransplant years, a high IPV was associated with inferior graft survival. Our data indicate that a fluctuating tacrolimus trough level at years 1, 2, and 3 posttransplant is a major problem in kidney transplantation.